Normy bezpečnosti a ochrany zdraví - Horčička, Aleš (Univerzita Pardubice, 2006)
This article deals with integrated management system and its components - quality, occupational health and safety and environmental management systems - implemented according to valid OHSAS and ISO standards into the firm. All these systems are evaluated from the view of their importance for achieving firm's strategic aims. The integrated system better contributes to firm's activities promotion not only in the Czech Republic, but also in other countries of the European Union.
Keywords: management jakosti; normy ISO; bezpečnost práce; ochrana zdraví; BOZP; integrované systémy